Is human life absurd? : a philosophical inquiry into finitude, value, and meaning - Belliotti, Raymond A., 1948- (Value Inquiry Book Series;, 2019)
In this work, Belliotti unravels the paradoxes of human existence. The purpose of this philosophical journey is to reveal paths for forging meaningful, significant, valuable, even important lives. By examining notions of The Absurd expressed within Search for the Holy Grail, The Seventh Seal, and The Big Lebowski, the author crafts a working definition of "absurdity." He then investigates the contributions of classical thinkers such as Shakespeare, Schopenhauer, Nietzsche, Kierkegaard, Tolstoy, Sartre, Camus, as well as philosophers such as Nagel, Feinberg, and Taylor. After arguing that human life is not inherently absurd, Belliotti examines the implications of mortality for human existence, the relationship between subjective and objective meaning, and the persuasiveness of several challenging contemporary renderings of meaningful human lives.